PERANCANGAN GRAFIS KEMASAN MAKANAN BURAYOT SEBAGAI OLEH-OLEH KHAS GARUT - Egi Anwari; Ella Meilani; Oktarina Prasetyowati (DeKaVe, 2017)
This research was made to redesign the packing of Burayot, a typical snack from Garut. Food packaging, in addition to serving as a food protector, can also be a medium for communicating related food product information, brand, positioning and product differentiation. Burayot is a typical snack of Garut made from raw rice flour, brown sugar and coconut milk. In its development appeared other flavors, such as pandanus, black rice, menthol, strawberries, sesame and cheese. Generally, families in the area of Leles Garut can make burayot, but not every family sells it as commercial product. There are some small medium enterprises (SME) that produce burayot as commercial snack with different brands, such as Mak Ijoh, Saboga and Bu Lilis. However, those SMES haven’t made packaging design as one of their concern in doing their business, yet. Saboga has fairly good sales distribution, the products can be easily found in several gift shops in Garut and Bandung. But, as mentioned before, this brand has not been considering the packaging design. Its packaging hasn’t shown strong visual identities to distinguish it from other products, and it also hasn’t contained information needed for a packaging. This research method is qualitative by using experimental approach in the form of packaging design through design stages, visual studies and visual styling. Several trials of packaging materials are constrained by the content of cooking oil in the burayot confectionery that is widely absorbed in paper materials. The addition of paper material to the packaging structure has not been successful, so the experiment focuses more on the packaging label appearance. The results of this study are expected to help SME producers, especially Sabay burayot snacks can have packaging with a strong identity and clear information, so that consumers are easier to distinguish with other gifts.